2019
DOI: 10.33258/birex.v1i4.477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agricultural Residues Based-Compost on the Yield of Amarantus hybridus L. (Amaranthaceae) in Gbado-Lite City, Nord-Ubangi (Democratic Republic of the Congo)

Abstract: An experimental study was conducted in Gbadolite city to develop composts from peanut (Groundnut) and maize residues alone or combined. The study found that plots modified with compost based on peanut (Groundnut)  residues combined with corn residues are of good quality compared to  non-waste compost combined and unamended plots as indicated by the average values of plant height (91.9±0.79 cm vs. 54.0±1.35 cm), diameter at the collar (12.66±0.47 mm vs. 9.00±1.41 mm); number of leaves ( 20.6±0.47 vs. 15.6±0.47)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The analysis of variation with a single classification criterion at the probability threshold of 0.05 and Duncan's test showed that there is a significant difference between the treatments. This amounts to saying that during this study the best treatments were flamed rejects and installed compost from rice husks; then those installed on substrates based on sawdust and finally, those planted on substrates made from slush and flamed which turned out to be different from the controls which are the shoots planted on sand under greenhouse conditions and not flamed (Matembe 2019;Ngbolua et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of variation with a single classification criterion at the probability threshold of 0.05 and Duncan's test showed that there is a significant difference between the treatments. This amounts to saying that during this study the best treatments were flamed rejects and installed compost from rice husks; then those installed on substrates based on sawdust and finally, those planted on substrates made from slush and flamed which turned out to be different from the controls which are the shoots planted on sand under greenhouse conditions and not flamed (Matembe 2019;Ngbolua et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…The town of Gbado-Lite (Figure 1) is located in the Umbrian ecoregion, a subset of the Northeastern Congolian lowland forests. This ecoregion is one of the 200 global priority terrestrial ecoregions known as the « G200 » [Ngbolua, 2018;Ngbolua, 2019a;Ngbolua, 2019b;Ngbolua, 2019c;Ngbolua, 2020a;Ngbolua, 2020b]. From a bioclimatic point of view, the city of Gbado-Lite belongs to the climatic type AW2 according to the classification of Köppen [Ngbolua, 2018;Ngbolua, 2019a;Ngbolua, 2019b;Ngbolua, 2019c;Ngbolua, 2020a;Ngbolua, 2020b].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…This ecoregion is one of the 200 global priority terrestrial ecoregions known as the « G200 » [Ngbolua, 2018;Ngbolua, 2019a;Ngbolua, 2019b;Ngbolua, 2019c;Ngbolua, 2020a;Ngbolua, 2020b]. From a bioclimatic point of view, the city of Gbado-Lite belongs to the climatic type AW2 according to the classification of Köppen [Ngbolua, 2018;Ngbolua, 2019a;Ngbolua, 2019b;Ngbolua, 2019c;Ngbolua, 2020a;Ngbolua, 2020b]. Rainfall is relatively abundant with an average of more than 1600 mm, insolation is low, i.e., 45% of total radiation of tropical energy.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The town of Gbado-Lite (Figure 1) is located in the Ubangian ecoregion, a sub-region of the Northeastern Congolian lowland forests. This ecoregion is one of the 200 global priority terrestrial ecoregions known as the G200 [Ngbolua, 2019a;Ngbolua, 2019b;Ngbolua, 2019c;Ngbolua, 2020a;Ngbolua, 2020b;Ngbolua, 2020].…”
Section: Study Areamentioning
confidence: 99%